LACAME 2006 : Proceedings of the 10th Latin American Conference on the Applications of the Mössbauer Effect (LACAME 2006) held in Rio de Janeiro, Brazil, 5-9 November 2006 - Larica, C. (Springer, 2017)
Proceedings of the 10th Latin American Conference on the Applications of the Mössbauer Effect, LACAME 2006, held in Rio de Janeiro City, Brazil, 5-9 November 2006. This volume demonstrates the way in which researchers, on a wide range of topics, many interdisciplinary, find the applications of the Mössbauer Effect an outstanding method whose results, sometimes unique, complements and improves the information obtained by other techniques to deepen the understanding of the matter under research. This volume comprises research papers recording original investigations on applications to diverse areas like archaeology, metallurgy, soil science, geology, industrial applications, new instrumentation, corrosion, and chemical applications. The papers present the latest scientific work of various regional investigators.